2008
DOI: 10.1111/j.1600-0579.2007.00492.x
|View full text |Cite
|
Sign up to set email alerts
|

Profile of the dentist in the oral healthcare team in countries with developed economies

Abstract: This paper confines itself to the description of the profile of a general dentist while outlining where the boundary between specialist and generalist may lie. The profile must reflect the need to recognize that oral health is part of general health. The epidemiological trends and disease variation of a country should inform the profile of the dentist. A particular tension between the provision of oral healthcare in publicly funded and private services may result in dentists practicing dentistry in different w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0
5

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 2 publications
0
25
0
5
Order By: Relevance
“…Sanz et al. also reported that the profile of dentists in economically developed countries should include both their soft and hard skills. Soft skill has also been found to be important enough that Smithers et al.…”
Section: What Are Soft Skills?mentioning
confidence: 99%
“…Sanz et al. also reported that the profile of dentists in economically developed countries should include both their soft and hard skills. Soft skill has also been found to be important enough that Smithers et al.…”
Section: What Are Soft Skills?mentioning
confidence: 99%
“…This trend underscores the importance of combining both appropriate medical training for dental professionals and increased competence in managing patients with systemic implications, with competence in the newest technological developments in restorative dentistry. Dental implant therapy is the clearest example of such a trend (1).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies aimed at identifying dentists' professional profiles from different perspectives [4,10,11]. Gender-related studies observed that women are more inclined to have a lower weekly workload owing to family commitments [10,11].…”
Section: Discussionmentioning
confidence: 99%
“…Descriptive analysis showed some universal characteristics of dentists' population elsewhere: predominance of women , high levels of professional involvement ( dentistry as main occupation and high weekly workload ), predominance of workers in private dental service , and a tendency toward specialization and concentration in large cities [4,5,10]. Bravo-Péres [1] found a similar situation in Spain in 2004 and Brown and Lazar [14] described how, in the United States of America, the decline in private practice started at the beginning of the 1990 s. In Brazil, a similar situation occurred at the same time when there was an increased demand and utilization of public dental services.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation